Visceral and subcutaneous adipose tissue volumes are cross-sectionally related to markers of inflammation and oxidative stress: the Framingham Heart Study - Pou, Karla M; Massaro, Joseph M; Hoffmann, Udo; Vasan, Ramachandran S; Maurovich-Horvat, Pal; Larson, Martin G; Keaney, Jr, John F; Meigs, James B; Lipinska, Izabella; Kathiresan, Sekar; Murabito, Joanne M; O'Donnell, Christopher J; et al. (Circulation (New York, N.Y.), 2007)
Excess adiposity is associated with greater systemic inflammation. Whether visceral adiposity is more proinflammatory than subcutaneous abdominal adiposity is unclear. We examined the relations of abdominal subcutaneous adipose tissue (SAT) and visceral adipose tissue (VAT), assessed by multidetector computerized tomography, to circulating inflammatory and oxidative stress biomarkers in 1250 Framingham Heart Study participants (52% women; age 60+/-9 years). Biomarkers were examined in relation to increments of SAT and VAT after adjustment for age, sex, smoking, physical activity, menopause, hormone replacement therapy, alcohol, and aspirin use; additional models included body mass index and waist circumference. SAT and VAT were positively and similarly (with respect to strength of association) related to C-reactive protein, fibrinogen, intercellular adhesion molecule-1, interleukin-6, P-selectin, and tumor necrosis factor receptor-2 (multivariable model R2 0.06 to 0.28 [SAT] and 0.07 to 0.29 [VAT]). However, compared with SAT, VAT was more highly associated with urinary isoprostanes and monocyte chemoattractant protein-1 (SAT versus VAT comparison: isoprostanes, R2 0.07 versus 0.10, P=0.002; monocyte chemoattractant protein-1, R2 0.07 versus 0.08, P=0.04). When body mass index and waist circumference were added to the models, VAT remained significantly associated with only C-reactive protein (P=0.0003 for women; P=0.006 for men), interleukin-6 (P=0.01), isoprostanes (P=0.0002), and monocyte chemoattractant protein-1 (P=0.008); SAT only remained associated with fibrinogen (P=0.01). The present cross-sectional data support an association between both SAT and VAT with inflammation and oxidative stress. The data suggest that the contribution of visceral fat to inflammation may not be completely accounted for by clinical measures of obesity (body mass index and waist circumference).